An outline of English literature - Rogers, Pat, 1938- (Oxford University Press, 1992)
Designed as an accessible outline of the history of English literature from Anglo-Saxon verse to the present day. Major figures such as Chaucer, Milton, Donne, Wordsworth, Dickens, Eliot and Auden are covered and a separate section is devoted to Shakespeare.